EFL Majors’ Knowledge of Career Paths and the Job Market for English Graduates in Costa Rica - Loría Sánchez, Gloriana (2022)
The present study sought to ascertain the knowledge of English as a Foreign Language (EFL) majors of their career path possibilities and the job market for English graduates in Costa Rica. A total of 47 senior English students completed a questionnaire. Main findings reveal inconsistencies in the knowledge of English majors of career paths and the job market in Costa Rica. Results also evince the undergraduates’ lack of familiarity with the services provided to help them improve their knowledge of those topics. Practical implications are discussed.